2009
DOI: 10.1007/s00421-009-1146-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anaerobic exercise on salivary cortisol, testosterone and immunoglobulin (A) in boys aged 15–16 years

Abstract: This study investigated the effect of repeated bouts of short-term, high-intensity cycling exercise on the salivary cortisol, testosterone and immunoglobulin (A) concentrations of 15-16 year old boys. Seventeen apparently healthy schoolchildren (aged 15.5 +/- 0.4 years) participated in this study. All participants completed 6 x 8 s sprints, interspersed with 30 s recovery intervals on a cycle ergometer. Using the passive drool method, salivary samples were taken before, and 5 min after, exercise. The group mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
3
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 50 publications
0
31
3
2
Order By: Relevance
“…A difference between maximum effort during running and cycling has been described for children, and may be explained by the fact that greater muscle mass is involved during running (28) . Also, previous studies have shown that cortisol levels increase even after short bouts of exercise (13) , and continue to increase after acute exercise has stopped (29) . In the present study, salivary cortisol levels not only remained unchanged or decreased immediately after the exercise test, but also, in the majority of the children, levels had not returned to pre-exercise levels 15 min after recovery.…”
Section: Discussionmentioning
confidence: 94%
“…A difference between maximum effort during running and cycling has been described for children, and may be explained by the fact that greater muscle mass is involved during running (28) . Also, previous studies have shown that cortisol levels increase even after short bouts of exercise (13) , and continue to increase after acute exercise has stopped (29) . In the present study, salivary cortisol levels not only remained unchanged or decreased immediately after the exercise test, but also, in the majority of the children, levels had not returned to pre-exercise levels 15 min after recovery.…”
Section: Discussionmentioning
confidence: 94%
“…The increase in its concentration in venous blood serum during physical work was observed by Matsuse et al (26) and by Madarame et al (24). These authors also emphasized high contribution of androgens to increase muscle mass caused by training (17,(36)(37)(38).…”
mentioning
confidence: 78%
“…Such hormones include testosterone and cortisol. Unbound to carrier proteins, free subfractions of each hormone appear in saliva and have the highest biological activity (12,15,21,28). Thus, as salivary testosterone and cortisol values are monitored in athletes over time, they may give an insight into the merits that various workouts have on a person's performance and health (5).…”
Section: Introductionmentioning
confidence: 99%